Decision-making during urgent phase of a nuclear accident under extreme conditions - Hussain, Mazzammal; Mehboob, Khurram; Ilyas, Syed Zafar; Shaheen, Saima (Safety science, 2023)
•We introduced a systematic decision-making process named ROSYNA, a real-time decision support system for a nuclear accident to be considered by the decision-makers during urgent phase of a nuclear accident under extreme conditions.•ROSYNA is a three-step approach i.e., evaluation of decision problem attributes, identification of situation and implementation of decision table.•A prototype applicability of ROSYNA was implemented to the Fukushima situation. We concluded that the decision problem attributes, which are the key element of this methodology need to be assessed using professional judgment based on the nature of the accident, the information that can be gleaned from the nuclear facility, radiation monitoring, and the prior understanding of such occurrences and pre-established response arrangements. Disasters when occurs result in a disruption of the normal life of society or community and have a severe impact on human life, health, environment, and social and economic activities. Ionizing radiations are a concern associated with nuclear accidents by their very nature, and managing a nuclear catastrophe adds additional pressure on decision-makers to address the immediate and long-term effects of ionizing radiations. Decision-making is more difficult during the early stages of a nuclear disaster because of the high level of uncertainty in the situation and the unavailability of detailed information. We introduce a systematic methodology named ROSYNA, a real-time decision support system for a nuclear accident to be considered for such an uncertain situation. The core of this decision support system is use of a decision table specific to various situations by assessing the decision problem attributes. The prototype applicability of the method was implemented to the Fukushima situation and a comparison was made with HERCA-WENRA and the IAEA approaches. With due consideration of uncertainties regarding the situation during the early phase of a nuclear emergency, we recommend considering the implementation of protective measures by utilizing the ROSYNA philosophy in the decision-making process. The decision problem attributes, which are the key element of this methodology need to be assessed using professional judgment based on the nature of the accident, the information that can be gleaned from the nuclear facility, radiation monitoring, prior understanding of such occurrences and pre-established response arrangements.